Black Panther [videorecording (DVD)] - Coogler, Ryan, 1986-; Boseman, Chadwick; Jordan, Michael B. (Michael Bakari), 1987-; Nyong'o, Lupita; Kirby, Jack (Buena Vista Home Entertainment, 2018)
King T'Challa returns home to the isolated, technologically advanced African nation of Wakanda to serve as new leader. However, T'Challa soon finds that he is challenged for the throne from divisions within his own country. When two enemies conspire to destroy Wakanda, the hero known as Black Panther must join forces with C.I.A. agent Everett K. Ross and members of the Wakandan Special Forces, to prevent Wakanda from being drawn into a world war.